2018
DOI: 10.1016/j.neuroscience.2018.03.024
|View full text |Cite
|
Sign up to set email alerts
|

Corticotropin-Releasing Factor in the Brain and Blocking Spinal Descending Signals Induce Hyperalgesia in the Latent Sensitization Model of Chronic Pain

Abstract: Latent sensitization is a model of chronic pain in which an injury triggers a period of hyperalgesia followed by an apparent recovery, but in which pain sensitization persists but is suppressed by opioid and adrenergic receptors. One important characteristic of latent sensitization is that hyperalgesia can be triggered by acute stress. To determine whether the effect of stress is mimicked by the activation of corticotropin-releasing factor (CRF) signaling in the brain, rats with latent sensitization induced by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 67 publications
0
23
0
Order By: Relevance
“…Contralateral latent sensitization is poorly understood, and possible mechanisms for future study include not only descending facilitation (Chai et al, 2012;Porreca et al, 2002;Taylor and Corder, 2014) and suppression of descending inhibition from brainstem nuclei (Chen et al, 2018), but also neuroimmune interactions (Cairns et al, 2015) and communication of reactive astrocytes through gap junction connexins (Gao and Ji, 2010), although neither naltrexone (Corder et al, 2013) nor LY2456302 ( Figure 7) induced pERK activation in astrocytes.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Contralateral latent sensitization is poorly understood, and possible mechanisms for future study include not only descending facilitation (Chai et al, 2012;Porreca et al, 2002;Taylor and Corder, 2014) and suppression of descending inhibition from brainstem nuclei (Chen et al, 2018), but also neuroimmune interactions (Cairns et al, 2015) and communication of reactive astrocytes through gap junction connexins (Gao and Ji, 2010), although neither naltrexone (Corder et al, 2013) nor LY2456302 ( Figure 7) induced pERK activation in astrocytes.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…The transition to chronic pain can also occur through another recently described mechanism known as “latent sensitization” (LS). LS is pathological pain following injury or inflammation that is “masked” during apparent recovery by endogenous opioid receptor function and “unmasked” by treatment with an opioid inverse agonist, such as naltrexone, or by stress [310]. In this study, we compare the effects of morphine and a novel opioid on both the paradoxical exacerbation of pain and on LS, with the goal of assessing the new analog for preventing the transition from acute to chronic pain.…”
Section: Introductionmentioning
confidence: 99%
“…Comprehensively described by Taylor [8], Corder [4], and Marvizon [3, 6], LS and endogenous dependence are best thought of as two sides of the same coin; the phenomena are inextricably linked and cause a susceptibility to unmasking pain through either stress or chemical inactivation of Mu-opioid receptor (MOR) constitutive activity. The initial pain insult activates pain pathways (“accelerator”) and descending pathways induce constitutive activity at the MOR (MOR CA ) to counteract pain (“brake”).…”
Section: Introductionmentioning
confidence: 99%
“…Hill (2000) suggested that the analgesic effects of NK1R antagonists could be due to their supraspinal effects on stress (Rupniak and Kramer, 2017). Indeed, stress induces hyperalgesia in rats with latent sensitization (Chen et al, 2018b;Rivat et al, 2007). However, in this study both RP67580 and NTX were given intrathecally, so it is unlikely that they had supraspinal effects.…”
Section: Failure Of Nk1r Antagonists In Clinical Trialsmentioning
confidence: 73%
“…Mechanical allodynia was measured with von Frey filaments (Touch-Test) using the twoout-of-three method (Chen et al, 2018b;Jarahi et al, 2014;Kingery et al, 2000;Michot et al, 2012;Walwyn et al, 2016). Measures were done by putting the rats in acrylic enclosures on an elevated metal grid (IITC Life Science Inc., CA), to which the rats were habituated for 30 min, daily for 3 days.…”
Section: Measures Of Mechanical Hyperalgesiamentioning
confidence: 99%